1116 Hyperglycaemia and Insulin-Induced Alterations in the Retina of Rat Pups. (October 2012) - Gyarmati, J; Szabadfi, K; Gabriel, R; Kiss, P; Reglodi, D; Mammel, B; Kvarik, T; Ertl, T
Abstract : Background and Aims: Rat pups are applicable to investigate specific role of the factors which are implicated in the pathogenesis of retinopathy of prematurity (ROP) including hyperglycaemia and insulin treatment. Methods: The aim of our study was to investigate specific effect of streptozotocin-induced hyperglycaemia, insulin-treatment and intravitreal injection of a potential retinoprotective agent, pituitary adenylate cyclase activating polypeptide (PACAP) on the rat pups' retina. We made a comparative analysis between the following treatment-groups: controls (Stz-/Ins-), insulin-treated (Stz-/Ins+), hyperglycaemic (Stz+/Ins-), insulin-treated hyperglycaemic (Stz+/Inz+); all animals were treated with intravitreal PACAP or vehicle. Blood glucose levels were monitored. The retinas were processed on P21 for routine histology and immunohistochemistry for glial fibrillary acidic protein (GFAP), GLUT1 and tyrosine hydroxylase (TH). Results: Standard histological methods revealed no major differences between the groups. Elevated expression of GFAP – as an aspecific marker of metabolic insults in the retina- was detected from the inner retina in the Stz-/Ins+ group, although hypoglycaemia didn't develop. Similar alteration of the GFAP staining was found in the hyperglycaemic (Stz+/Ins-) and insulin-treated hyperglycaemic (Stz+/Inz+) groups. Intravitreal PACAP resulted in suppression of the elevated GFAP expression in the Stz-/Ins+ group, but not in the Stz+/Ins-, and Stz+/Inz+ ones. None of the groups showed alteration in the anti-TH immunoreactivity (dopaminergic amacrine cells) or GLUT1 expression of pigment epithelial cells. Conclusions: In our model hyperglycaemia or insulin did not induce ROP; however, sign of metabolic insult was detected in the neural retina, which was partly prevented by intravitreal PACAP application.